Educational and Motivational Predictors of Academic Achievement (Based on PISA 2018 Reading Data) - T.O. Gordeeva; O.A. Sychev (Психологическая наука и образование, 2024)
Academic achievements of teenage students are an important indicator of their further success and adaptation to life in adult society. The material of the study was the data collected for the international project PISA 2018 on a representative sample of Russian teenagers (N=7608). The article presents the results of studying the role of educational and motivational factors (controlling for gender and family environment) of academic achievements of Russian teenagers based on the material of PISA 2018 on reading literacy. We confirmed that regarding the environmental (family and teacher) factors in the academic achievements of schoolchildren, the role of SES as an important predictor of schoolchildren's academic achievements, the role of teacher support for active involvement in reading is significantly positive factor, and Teacher-directed instruction is negative factor. The study confirmed an important contribution of motivational variables to reading literacy, reading engagement was proved to be a positive predictor, and fixed mindset about intelligence was proved to be a negative predictor of reading literacy competence. The discussion shows that the data obtained generally corresponds to international data on predictors of academic achievement among schoolchildren based on the PISA 2018. The results obtained can be used in the context of teacher training and for improving the quality of education in Russian schools.